Uji Toksisitas Ekstrak Berbasis Nades dari Daun Kadamba (Mitragyna Speciosa Korth) terhadap Mencit (Mus Musculus): Toxicity of Nades-Based Extract From Kadamba Leaf (Mitragyna Speciosa Korth) on Mice (Mus Musculus) - Fauzan Afandi; Vita Olivia Siregar; Islamudin Ahmad (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Traditionally, kadamba leaves have benefits for treating diarrhea, diabetes, pain, rheumatism, gout and have been scientifically proven to be antinociceptive and inhibit T47D breast cancer cells. This study aims to determine the toxicity of NADES-based extract from kadamba leaves by looking at the LD50 value and its effect on body weight and behavior of mice. The 15 mice used were divided into 5 groups with 3 mice in each group. The NADES-based extract from kadamba leaves was given orally with various doses of 4000 mg/KgBB, 8000 mg/KgBB, 16000 mg/KgBB, and 32000 mg/KgBB and one group was given a solvent. Each group was observed for 30, 60, 120, 180, and 240 minutes after administration of the extract and the observations were continued for 14 days to observe toxic symptoms, changes in body weight and death. Based on the results of the study, no deaths were found in the solvent group, 4000 mg/KgBB, and 8000 mg/KgBB. For the group with a dose of 16000 mg/KgBW, 2 mice died and the group with a dose of 32000 mg/KgBW found the death of 3 mice, so the LD50 value obtained was 14.256 g/KgBW which was included in the practically non-toxic category.